2013
DOI: 10.1111/crj.12037
|View full text |Cite
|
Sign up to set email alerts
|

Dysanaptic growth of lung and airway in children with post‐infectious bronchiolitis obliterans

Abstract: PFT in childhood PBO was characterized by significant airway obstruction. Over time, FVC (lung parenchyma) increased and FEV1 (airway) remained stable, but FEV1/FVC ratio declined more than expected, suggesting a mismatch in the growth of the airway and lung parenchyma (dysanaptic growth). Further studies in larger populations are needed to validate these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
4
19
0
2
Order By: Relevance
“…Mosquera R. et al informed that over time, FVC (lung parenchyma) increased and FEV1 (airway) remained stable, suggesting a mismatch in the growth of the airway and lung parenchyma, dysanaptic growth. Afterwards, one larger study was performed, in which 46 patients were followed for an average of 12.5 years, confirming previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquera R. et al informed that over time, FVC (lung parenchyma) increased and FEV1 (airway) remained stable, suggesting a mismatch in the growth of the airway and lung parenchyma, dysanaptic growth. Afterwards, one larger study was performed, in which 46 patients were followed for an average of 12.5 years, confirming previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…The same process may occur after lobar resection due to compensatory growth of the remaining lung parenchyma. The mismatch in the growth of the airways and pulmonary parenchyma, called dysanaptic growth, has also be shown to be the cause of changes in pulmonary function tests in babies with post infectious lung diseases . The hypothesis that minor abnormalities affect also the macroscopically non‐affected lung is supported by the findings that also patients with extralobar BPS, where only sequestrectomy is performed, present respiratory sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…A recent follow-up study of lung function in children with PIBO over a period of 35 months (range, 24-82 months) reported increased FVC and stable FEV 1 over time, resulting in a decline in the FEV 1 /FVC ratio, which suggests dysanaptic growth 31) . In addition, the authors reported persistent neutrophilic inflammation several years after the onset of disease in the absence of overt infection, as assessed by microbiological analysis.…”
Section: The Duration Of Inflammation After the Insult In Children Wimentioning
confidence: 99%
“…In addition, it has been suggested that azithromycin, a macrolide antibiotic with anti-inflammatory properties, may be beneficial for the progression of BOS after LT or HSCT, however, the results are controversial 47 48 49 50) . In children with PIBO, azithromycin has been used clinically without supporting evidence 31) .…”
Section: Treatmentmentioning
confidence: 99%